GEOCHEMISTRY OF CENOZOIC MICROTEKTITES AND CLINOPYROXENE-BEARING SPHERULES - Glass B.P.; Huber H.; Koeberl C. (My University, 2004)
We have determined the major and trace element compositions of 176 individual microtektites/spherules from the Australasian, Ivory Coast, and North American microtektite and clinopyroxene-bearing (cpx) spherule layers. Trace element contents for up to 30 trace elements were determined by instrumental neutron activation analysis (INAA), and major element compositions were determined using energy dispersive X-ray (EDX) analysis in combination with a scanning electron microscope (SEM). In addition, petrographic data were obtained for the cpx spherules using the SEM and EDX. This is the first trace element study of individual Australasian microtektites, and the data revealed the presence of a previously unrecognized group of Australasian microtektites with high contents of Ni (up to 471 ppm). In previous studies the high-Mg (HMg) Australasian microtektites were thought to be related to the HMg Australasian tektites, but our trace element data suggest that the high-Ni (HNi) Australasian microtektites, rather than the high-Mg microtektites, are related to the high-Mg Australasian tektites. We find that Cenozoic microtektites/spherules from a given layer can be distinguished from microtektites/spherules from other layers as a group, but it is not always possible to determine which layer an individual microtektite/spherule came from based only on trace element compositions. The cpx spherules and most of the microtektites have Cr, Co, and Ni contents that are higher than the average contents of these elements in the upper continental crust, suggesting the presence of a meteoritic component. The highest Cr, Co, and Ni contents are found in the cpx spherules (and low-Si cpx-related microtektites). Unetched to slightly etched cpx spherules have Ni/Cr and Ni/Co ratios that generally lie along mixing curves between the average upper continental crust and chondrites. The best fit appears to be with an LL chondrite.
Keywords: Cenozoic; Cenozoic; Кайнозой